Response of nigella (Nigella sativa L) variety NRCSS AN 1 to different agro-tech- niques - B B Vashishtha, S K Malhotra, (Journal of Spices and Aromatic Crops, 2008)
A field study was conducted during the winter seasons of 2002-2003 and 2003-2004 to studythe response of nigella (Nigella sativa L.) variety NRCSS AN-1 to different agro-techniquesunder semi-arid conditions. The yield attributes viz. number of capsules/plant, number ofseeds/capsule and 1000 seed weight were significantly high when crop was sown on 15 Octoberfollowed by 1 October sowing. Significantly higher seed yield of 8.84 q/ha was recordedwhen crop was sown on 15 October. The seed yield of 7.86 q/ha was significantly higherwith row spacing of 30 cm. The plant height and number of branches/plant were more atseed rate of 7 and 8 kg/ha and were noticed significantly high as compared to seed ratetreatment of 9 kg/ha. However, the seed yield attributes and seed yield (8.24 q/ha) weresignificantly high at seed rate of 8 kg/ha. The fertilizer dose of 50 kg N, 25 kg P2O5 and 20 kgK2O /ha was found optimum and produced higher seed yield of 7.87 q/ha. The days to 50%flowering was not affected considerably with different treatments. The essential oil contentincreased significantly when crop was sown at wider spacing of 40 cm and with applicationof fertilizer dose of 50 kg N, 25 kg P2O5 and 20 kg K2O /ha.